RESPONSIBILITY OF BIG TECH IN THE PROTECTION OF CHILDHOOD, LEGAL ANALYSIS OF THE DUTY OF CARE OF DIGITAL PLATFORMS REGARDING THE RIGHTS OF CHILDREN AND ADOLESCENTS (REMUNOM, 2026)
The advancement of digital technologies and the increasing presence of children and adolescents in virtual environments have intensified legal and academic debates regarding the protection of childhood on the internet. In this context, this study analyzes the responsibility of digital platforms in protecting children and adolescents in the online environment, considering challenges related to digital safety, the circulation of potentially harmful content, and the role of technology companies in platform governance and content moderation. The objective of this research is to investigate how big techs can be held responsible for safeguarding vulnerable users in digital environments, particularly in light of the fundamental rights of children. Methodologically, the study adopts a qualitative approach based on a literature review of recent scientific publications addressing digital governance, child protection online, and platform accountability. The results indicate that protecting children in digital environments requires stronger regulatory mechanisms, greater transparency in algorithmic systems, and the implementation of effective content moderation policies by digital platforms. It is concluded that the responsibility of technology companies is a central element in the construction of safer digital environments, requiring the articulation of state regulation, platform governance, and educational strategies aimed at promoting responsible internet use.